As redes de escrituras nas periferias de São Paulo: a palavra como manifestação de cidadania - Bin, Marco Antonio (2009)
The objective of the work is to examine the processes which take the resident population of the suburbs of São Paulo to participate in the evenings poetics, produce which marginal texts (lyrical and prosaic). And in that case, evoking it as well, in what as the poetic performance is established. It indeed amuses with the recitations. My object of study is two evenings poetic, situated in the sector of the Southwest of São Paulo: that of Cooperifa (Chácara Santana, district of M' Boi Mirim) and that of Binho (Campo Limpo, homonymous district). My theoretical references includes the literature which analyzes the concept of territory and the processes of social and space organization in the city of São Paulo of the circles of the century XX in our days, when I remove the aspects of the urban segregation. As examine the methodology, I try to analyze the territory of the city, the evolution of the reproduction of the space along time, for then to carry out an approach of the pedaço, the quebrada, the place where the writing eccentric is unfolded. I try then to discuss the forms of this act, its appeal to a peripheral identity, her poetic performance, finishing with their unfolding in deprived territories of the city, as cultural events for besides evenings